2013
DOI: 10.1159/000355248
|View full text |Cite
|
Sign up to set email alerts
|

Hypovascular Hepatic Nodules Showing Hypointense on the Hepatobiliary-Phase Image of Gd-EOB-DTPA-Enhanced MRI to Develop a Hypervascular Hepatocellular Carcinoma: A Nationwide Retrospective Study on Their Natural Course and Risk Factors

Abstract: Objective: We aimed to investigate the natural outcome of nonhypervascular lesions detected in the hepatobiliary phase of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced MRI by performing a longitudinal study retrospectively enrolled in a nationwide manner. Methods: Between February 2008 and March 2011, 224 patients with 504 nodules that were diagnosed as nonhypervascular by imaging were recruited from institutions that participated in the present study. We examined the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
1
30
1
Order By: Relevance
“…This is in contrast to the results of several previous studies [50,51,55] which demonstrated that hyperintensity on T2WI or hyperintensity on DWI in hypovascular hypointense nodules on HBP gadoxetic acid-enhanced MRI in patients with cirrhosis was strongly associated with progression to hypervascular HCC. The discrepancy between the previous studies [50,51] and the current study may be related to the different tumor sizes between the study patients; we included HBP hypointense nodules ≥1 cm, but the previous studies included sub-centimeter nodules.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the results of several previous studies [50,51,55] which demonstrated that hyperintensity on T2WI or hyperintensity on DWI in hypovascular hypointense nodules on HBP gadoxetic acid-enhanced MRI in patients with cirrhosis was strongly associated with progression to hypervascular HCC. The discrepancy between the previous studies [50,51] and the current study may be related to the different tumor sizes between the study patients; we included HBP hypointense nodules ≥1 cm, but the previous studies included sub-centimeter nodules.…”
Section: Discussioncontrasting
confidence: 99%
“…It is now known that when such nodules follow their natural course, many eventually become hypervascular and progress to classical hypervascular HCC [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. For these reasons, it has recently become a reality in the diagnosis of early HCC that among existing imaging diagnostic modalities, EOB-MRI is achieving a level of diagnostic performance approaching that of liver pathology experts.…”
Section: Establishment Of the Concept Of Early Hccmentioning
confidence: 99%
“…Previous studies have shown that the hypovascular hypointense nodules develop into hypervascular HCCs at 1-year cumulative progression rates of 15.5% [37] and 14.9% [38] for average tumor sizes of 8.4 mm and 9.3 mm, respectively, but this increased to 43.5% [39] for an average tumor size of 14 mm. In addition, the imaging and clinical features for early progression of hypovascular hypointense nodules to hypervascular HCCs include hyperintensity at DWI [32,38], hyperintensity in T2-weighted images, and a treatment history for HCC [34,38]. …”
Section: Consensus Statementsmentioning
confidence: 99%
“…Inoue et al [38] used CEUS with Sonazoid® to evaluate the treatment response of HCC after RFA, finding that the assessment of CEUS for a complete or incomplete ablated response was comparable with that of dynamic CT. Therefore, CEUS can be used to assess the efficacy of RFA for HCC, with the potential to reduce the number of CT scans required for confirmation.…”
Section: Consensus Statementsmentioning
confidence: 99%